Digital Social Influence and Its Impact on the Attitude of Organic Product Consumers. - García-Roldán, G. (2025)
Social media has become a tool that exerts a significant influence on consumer behavior. In this sense, this study aims to identify whether digital social influence derived from the informational nature of social media content and online member group support influences the subjective norms and environmental attitudes of organic product consumers. This study was developed using a quantitative, correlational, and cross-sectional design. A total of 371 organic product consumers participated in the study, who were administered a questionnaire consisting of 17 questions measured on a 5-point Likert scale. Statistical analysis was performed using SPSS 24 and Smart PLS, and convergent validity, discriminant validity, and structural equation modeling were applied. The results of the study identified that environmental attitudes continue to be a highly influential factor in organic product purchasing behaviors and that these attitudes are shaped by subjective norms and digital social influencers, such as social media content and online member support groups. Furthermore, the study found that subjective norms mediate the relationship between environmental attitudes and social media content as well as online member support groups. Beyond contributing to the theoretical understanding of environmental attitudes, this study offers practical insights into designing digital marketing strategies that leverage social influence to promote sustainable consumption, particularly in emerging markets.